The Effect of Shopeepay E-Wallet Use On Shopeepay User Satisfaction and Loyalty in Tangerang City - Azzahra Baby Dwi Putri; Nur Fitri Dewi; Noviyanti Noviyanti (International Publisher (YAPENBI), 2026)
This study aims to analyze the effect of e-wallet usage on ShopeePay user loyalty in Tangerang, mediated by user satisfaction. In this study, the researcher used a quantitative research type with a survey method. This study applied a questionnaire as the research instrument measured using a Likert scale. The sampling method for this study was non-probability sampling with a purposive sampling technique using sample criteria, namely ShopeePay users living in Tangerang City.The collected data were processed using Statistical Package for the Social Sciences (SPSS) software. The results of the study indicate that partially e-wallet usage (X) has a positive and significant effect on ShopeePay user satisfaction (Z) in Tangerang. However, user satisfaction (Z) has a positive and insignificant effect on ShopeePay user loyalty (Y) in Tangerang. Then, based on the results of the path analysis, it shows that e- wallet usage has a positive and significant effect on ShopeePay user loyalty in Tangerang through user satisfaction. The results of the coefficient of determination show that partially the use of e-wallet (X) has an effect on user loyalty (Y) of 15.7%, then simultaneously the variable of e-wallet use (X) through user satisfaction (Z) has an effect on user loyalty (Y) of 73.9%.